1998
DOI: 10.1093/ajcn/67.5.885
|View full text |Cite
|
Sign up to set email alerts
|

Energy utilization and growth in breast-fed and formula-fed infants measured prospectively during the first year of life

Abstract: This study is the first to report approximations of energy requirements for male and female breast-fed and formula-fed infants based on individual estimates of total daily energy expenditure (TDEE) and energy deposition derived from total body fat (TBF) and fat-free mass (FFM) gain as determined by total-body electrical conductivity. In 46 healthy, full-term infants the effect of > or = 4 mo of exclusive breast-feeding compared with formula feeding on macronutrient and energy intake, TDEE, energy deposition, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
24
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(30 citation statements)
references
References 28 publications
6
24
0
Order By: Relevance
“…On average, %TBF in the 9-month-old infants is similar to the corresponding figure presented by Davies et al (1997), but higher than that reported by Butte et al (2000a). Percentage TBF in the 14-month-old children is higher than corresponding figures presented by others for 12-month-old children (Davies et al, 1997;de Bruin et al, 1998;Butte et al, 2000a).…”
supporting
confidence: 69%
See 1 more Smart Citation
“…On average, %TBF in the 9-month-old infants is similar to the corresponding figure presented by Davies et al (1997), but higher than that reported by Butte et al (2000a). Percentage TBF in the 14-month-old children is higher than corresponding figures presented by others for 12-month-old children (Davies et al, 1997;de Bruin et al, 1998;Butte et al, 2000a).…”
supporting
confidence: 69%
“…This is similar to figures reported by Butte et al (2000b), which were 320 AE 40 and 340 AE 50 kJ=kg=day for 9-month-old girls and boys, respectively, and 330 AE 50 and 340 AE 40 kJ=kg=day for 12-month-old girls and boys, respectively. Corresponding figures reported by de Bruin et al (1998) were 320 AE 35 and 343 AE 42 kJ=kg=day for 8-month-old girls and boys, respectively, and 323 AE 27 and 341 AE 35 kJ= kg=day for 12-monthold girls and boys, respectively. Davies et al (1997) presented slightly lower average figures, ie 306 AE 62, 308 AE 55, 325 AE 64 and 322 AE 56 kJ=kg=day for 9-month-old girls, 9-month-old boys, 12-month-old girls and 12-month-old boys, respectively.…”
mentioning
confidence: 54%
“…Breast-fed infants appear to have lower requirements than formula-fed infants (Butte, 1996), as has been shown from various studies on energy expenditure using the doubly labelled water method (Davies et al, 1990;De Bruin et al, 1998;Salazar et al, 2000). Butte et al (1990) compared sleeping metabolic rate in breast-and formula-fed babies and found higher values in the latter group.…”
Section: Discussionmentioning
confidence: 79%
“…Initially, energy requirement is mainly determined by growth and energy expenditure for body maintenance. 1 Activity energy expenditure as a fraction of TEE increases from 20% at age 1 to~35% at age 18. 2 The increase is reflected in an increase of the physical activity index (PAI = TEE/ REE) from 1.4 to 1.75.…”
Section: Body Size Body Composition and Energy Expenditurementioning
confidence: 98%